Minimizing the Adversely Impacts of Water Deficit and Soil Salinity on Maize Growth and Productivity in Response to the Application of Plant Growth-Promoting Rhizobacteria and Silica Nanoparticles - Emad M. Hafez; Hany S. Osman; Salah M. Gowayed; Salah A. Okasha; Alaa El-Dein Omara; Rokayya Sami; Ahmed M. Abd El-Monem; Usama A. Abd El-Razek (Agronomy, 2021)
The development of new approaches for sustaining soil quality, leaf health, and maize productivity are imperative in light of water deficit and soil salinity. Plant growth-promoting rhizobacteria (PGPR) and silica nanoparticles (SiNP) are expected to improve soil chemistry leading to improved plant performance and productivity. In this field experiment, water deficit is imposed by three irrigation intervals—12 (I1), 15 (I2), and 18 (I3) days. Plants are also treated with foliar and soil applications (control, PGPR, SiNP, and PGPR + SiNP) to assess soil enzymatic activity, soil physicochemical properties, plant physiological traits, biochemical analysis, nutrient uptake, and productivity of maize (Zea mays L.) plants grown under salt-affected soil during the 2019 and 2020 seasons. With longer irrigation intervals, soil application of PGPR relieves the deleterious impacts of water shortage and improves yield-related traits and maize productivity. This is attributed to the improvement in soil enzymatic activity (dehydrogenase and alkaline phosphatase) and soil physicochemical characteristics, which enhances the plants’ health and growth under longer irrigation intervals (i.e., I2 and I3). Foliar spraying of SiNP shows an improvement in the physiological traits in maize plants grown under water shortage. This is mainly owing to the decline in oxidative stress by improving the enzymatic activity (CAT, SOD, and POD) and ion balance (K+/Na+), resulting in higher photosynthetic rate, relative water content, photosynthetic pigments, and stomatal conductance, alongside reduced proline content, electrolyte leakage, lipid peroxidase, and sodium content under salt-affected soil. The co-treatment of SiNP with PGPR confirms greater improvement in yield-related traits, maize productivity, as well as nutrient uptake (N, P, and K). Accordingly, their combination is a good strategy for relieving the detrimental impacts of water shortage and soil salinity on maize production.